Prebiotic, Immunomodulating, and Antifatigue Effects of Konjac Oligosaccharide. Issue 12 (4th December 2018) - Zeng, Yan; Zhang, Jiangang; Zhang, Ying; Men, Yan; Zhang, Bo; Sun, Yuanxia
Abstract: Irregular and long time work schedules not only makes people feel fatigue, but also brings great risks of diseases, due to gastrointestinal disorder and immune dysfunction. Therefore, it has positive significance to help challenged people stay energetic and healthy with food supplement. Konjac oligosaccharide has shown various physiological benefits and been recommended in the fortification of functional foods. However, there have been few reports on its application aimed to simultaneously relieve physical fatigue and keep body healthy. In this paper, the potential prebiotic, immunoregulatory, and antifatigue activities of konjac oligosaccharide were evaluated in vitro and in vivo . The results showed that konjac oligosaccharide could promote probiotics growth and short chain fatty acids production in mice cecum. At the concentration of 50 to 200 μg/mL, konjac oligosaccharide could activate murine macrophage RAW 264.7 to secret NO and cytokines of IL‐10 and IL‐6. Moreover, this oligosaccharide could alleviate physical fatigue by prolonging exhaustive time, improving the level of superoxide dismutases and glutathione peroxidase, increasing the content of blood glucose, and decreasing the content of blood urea nitrogen. The results suggested that konjac oligosaccharide had prebiotic, immunoregulatory, and antifatigue effects, providing its application potential in functional food aimed at people with irregular and long time work.